Enhancing Renewable Energy Power Generation through the Exploration of Laser Technology - Ma'arif, Syamsul; Kulla, Irwanuddin H. I.; Yunita, Lia (Proklamasi 45 University, 2023)
This research aims to investigate the utilization of laser technology in improving the performance of power generation systems from renewable energy sources, focusing on solar, wind, hydropower, and biomass energy. A literature review and comprehensive analysis were conducted using a descriptive and synthetic data analysis method. The discussion results indicate that laser technology can significantly contribute to the utilization of renewable energy. In solar power generation systems, laser technology enhances solar radiation absorption in solar thermophotovoltaics applications and flexible solar panel designs. In wind power generation systems, laser technology is employed in long-range wind flow measurement using LiDAR, wind turbine load validation, and improving wind turbine control. In hydropower generation systems, laser technology protects and monitors water turbine blades to prevent erosion and damage. In biomass power generation systems, laser technology is employed for chemical element detection in the energy conversion process and analysis of biomass properties. In conclusion, using laser technology in power generation from renewable energy sources offers significant potential for enhancing efficiency, performance, sustainability, and environmental friendliness.